Pengaruh Penggunaan Aplikasi Game Educaplay (Froggy Jumps) Terhadap Hasil Belajar Matematika Siswa Kelas IV di SDN 023905 Binjai Utara - Qonita Mujahidah; Elvi Mailani (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to determine the effect of the use of the educaplay game application (froggy jumps) on the mathematics learning outcomes of fourth grade elementary school students. This study is a quantitative study with a Quasi Experiment NonEquivalent Control Group research design. In this design, there are two groups: one experimental group that receives treatment and one control group that does not. The population in this study was 46 students with a purposive sampling technique and the sample was 23 students. data collection techniques in this study used interviews, observations, and tests. The data analysis technique in this study used the independent t test. Based on the output of "Test Statiscs" the Asymp.sig value (2-tailed) was obtained at 0.000≤0.05, which can be concluded that "The hypothesis is accepted". Thus, it can be said that there is a difference between the experimental class and the control class. Because of the significant difference, it can be concluded that the use of the educaplay game application (froggy jumps) has an effect on mathematics learning outcomes in fourth grade SDN 023905 North Binjai